The Economic Security of Bank: Theoretical Basis and Systemic Approach - Gavlovska Nataliia I. (Bìznes Inform, 2017)
The article analyzes the existing approaches to interpreting the category of «economic security of bank». A author’s own definition of the concept of «economic security of bank» has been proposed, which should be understood as condition of protecting the vital interests of bank, achieved by harmonizing relationships with the entities of external influence and optimizing the internal system processes, thus enabling efficient function as well as development by means of an adaptation mechanism. A number of approaches to understanding the substance of the above concept has been allocated and their main characteristics have been provided. The need to study the specifics of interaction of banking institutions with the external environment in the context of interaction between the State agents and market actors has been underlined. Features of formation of the term of «system» have been defined, three main groups of approaches to interpretation of the term have been provided. A author’s own definition of the concept of «economic security system of bank» has been proposed. A concrete definition of principles for building an economic security system of bank has been provided.